Silencing CCR2 in Macrophages Alleviates Adipose Tissue Inflammation and the Associated Metabolic Syndrome in Dietary Obese Mice - Jongkil Kim; Kunho Chung; Changseon Choi; Jagadish Beloor; Irfan Ullah; Nahyeon Kim; Kuen Yong Lee; Sang-Kyung Lee; Priti Kumar (Elsevier, 2016)
Adipose tissue macrophage (ATM)-mediated inflammation is a key feature contributing to the adverse metabolic outcomes of dietary obesity. Recruitment of macrophages to obese adipose tissues (AT) can occur through the engagement of CCR2, the receptor for MCP-1 (monocyte chemoattractant protein-1), which is expressed on peripheral monocytes/macrophages. Here, we show that i.p. administration of a rabies virus glycoprotein-derived acetylcholine receptor-binding peptide effectively delivers complexed siRNA into peritoneal macrophages and ATMs in a mouse model of high-fat diet-induced obesity. Treatment with siRNA against CCR2 inhibited macrophage infiltration and accumulation in AT and, therefore, proinflammatory cytokines produced by macrophages. Consequently, the treatment significantly improved glucose tolerance and insulin sensitivity profiles, and also alleviated the associated symptoms of hepatic steatosis and reduced hepatic triglyceride production. These results demonstrate that disruption of macrophage chemotaxis to the AT through cell-targeted gene knockdown strategies can provide a therapeutic intervention for obesity-related metabolic diseases. The study also highlights a siRNA delivery approach for targeting specific monocyte subsets that contribute to obesity-associated inflammation without affecting the function of other tissue-resident macrophages that are essential for host homeostasis and survival.